Bacteriocinogenic Bacillus spp. Isolated from Korean Fermented Cabbage (Kimchi)—Beneficial or Hazardous? - Joanna Ivy Irorita Fugaban; Jorge Enrique Vazquez Bucheli; Wilhelm Heinrich Holzapfel; Svetoslav Dimitrov Todorov (Fermentation, 2021)
Bacillus velezensis ST03 and ST32, Bacillus amyloliquefaciens ST06 and ST109, and Bacillus subtilis ST08 were isolated from artisanal-produced kimchi and were identified based on 16S rRNA partial sequencing. DNA obtained from the investigated bacilli generated positive results for lichenicidin, iturin, subtilosin, and surfactin on a strain-specific basis. The strains were found to produce antimicrobial metabolites with activity levels ranging between 800 and 1600 AU/mL on a strain-specific basis, as determined against Listeria monocytogenes ATCC15313. Moreover, all tested strains in this study were still active after treatment with proteolytic enzymes, even with reduced inhibition zones compared to the controls, pointing to additional antimicrobial activity possibly related to a non-proteinaceous molecular structure. Most probably these strains may express surfactin as an additional factor in their complex antimicrobial activity. B. amyloliquefaciens ST09 and B. velezensis ST03 and ST32 were characterized as positive for β-hemolysis. B. subtilis ST08 was shown to be positive for hblC and nheC and B. amyloliquefaciens ST109 for nheB. B. amyloliquefaciens ST109 generated positive results for gelatinase activity. The ability of the studied Bacillus strains to metabolize different carbohydrate sources was done based on the API50CHB test, while the enzyme production profile was recorded by the APIZym kit. All studied strains were positive producers for biogenic amines production. Studied Bacillus spp. strains were resistant to some of the evaluated antibiotics, tested according to recommendations of CLSI and EFSA.